SARS-CoV-2 pathophysiology and its clinical implications: An integrative overview of the pharmacotherapeutic management of COVID-19. (December 2020) - Tsatsakis, Aristides; Calina, Daniela; Falzone, Luca; Petrakis, Dimitrios; Mitrut, Radu; Siokas, Vasileios; Pennisi, Manuela; Lanza, Giuseppe; Libra, Massimo; Doukas, Sotirios G.; Doukas, Panagiotis G.; Kavali, Leena; et al.
Abstract: Common manifestations of COVID-19 are respiratory and can extend from mild symptoms to severe acute respiratory distress. The severity of the illness can also extend from mild disease to life-threatening acute respiratory distress syndrome (ARDS). SARS-CoV-2 infection can also affect the gastrointestinal tract, liver and pancreatic functions, leading to gastrointestinal symptoms. Moreover, SARS-CoV-2 can cause central and peripheral neurological manifestations, affect the cardiovascular system and promote renal dysfunction. Epidemiological data have indicated that cancer patients are at a higher risk of contracting the SARS-CoV-2 virus. Considering the multitude of clinical symptoms of COVID-19, the objective of the present review was to summarize their pathophysiology in previously healthy patients, as well as in those with comorbidities. The present review summarizes the current, though admittedly fluid knowledge on the pathophysiology and symptoms of COVID-19 infection. Although unclear issues still remain, the present study contributes to a more complete understanding of the disease, and may drive the direction of new research. The recognition of the severity of the clinical symptoms of COVID-19 is crucial for the specific therapeutic management of affected patients. Graphical abstract: Image 1 Highlights: Respiratory system is the main target of SARS-CoV-2. SARS-CoV-2 infection can also affect the gastrointestinal tract, liver and pancreatic functions. SARS-CoV-2 can cause central and peripheral neurological manifestations. SARS-CoV-2 can affect the cardiovascular system and promote renal dysfunction. Cancer patients are at a higher risk of contracting the SARS-CoV-2 virus.